Implementation of Law No. 22 of 2022 Concerning Corrections in Connection with the Development of Juvenile Prisoners at the Class IIB Lubuk Pakam Correctional Institution - Wahyudi, Dedy; Warman, Syafril; Akmal, Akmal (Judge : Jurnal Hukum, 2024)
The Class IIB Lubuk Pakam Correctional Institution has fulfilled the rights of prisoners in accordance with the rules in Article 9 and Article 10 of Law Number 22 of 2022 concerning Corrections. These efforts are implemented through coaching and mentoring activities. The form of guidance is in the form of spirituality, guidance on social activities, counseling or health seminars, and also work guidance. In addition, this guidance is carried out by providing service innovation, supporting infrastructure and developing existing facilities to be maximized. Class IIB Correctional Institution Lubuk Pakam runs the correctional system by means of; implementation of change management, structuring the administration, human resource management system, strengthening accountability, strengthening supervision and improving the quality of service to the public. Class IIB Lubuk Pakam Correctional Institution which seeks to improve public service standards through the implementation of change management components, structuring procedures, human resource management systems, strengthening accountability, strengthening supervision and improving the quality of service to the public. Therefore, the feasibility of occupancy should be the main thing that can affect the quality of the correctional system in place.